Genetic diversity and evolution of endogenous pararetroviruses across Solanaceae: How farming systems drive dynamic tomato EPRVS changes under salt stress - Zitouna, Nadia; Sakka, Hela; Bouteraa, Mohamed Taieb; Mehrez, Marwa; Slatni, Tarek; Fakhfakh, Hatem; Ben Hamed, Karim; Gorsane, Faten (Frontiers in Plant Science, 2026)
IntroductionEndogenous pararetroviral sequences (EPRVs) expand plant genome plasticity and may serve as reservoirs for adaptive evolution. Most have undergone rearrangements and mutations, leaving them largely inactive. While their integration is generally neutral, biotic and abiotic stresses can occasionally reactivate EPRVs, triggering spontaneous infections. Plants counter this by suppressing expression through sequence degeneration, fragmentation, and epigenetic silencing mechanisms such as DNA methylation.MethodsEPRVs were detected using PCR across the Solanaceae family. Genomic segments were characterized through PCR amplification, sequencing, and analyses of genetic diversity and evolutionary parameters. Two salt-contrasting tomato genotypes were cultivated under saline conditions using two farming strategies, including monocropping and intercropping with halophyte plants. The distribution of EPRVs was performed using quantitative PCR, and the methylation status was assessed through bisulfite treatment followed by PCR amplification, cloning and sequencing.ResultsA Comparative analysis of genetic diversity revealed differential variability in the intergenic (IGR) region and the capsid–movement protein junction (CP-MP), likely reflecting distinct selective constraints. Haplotype networks inferred from the sequences, along with neutrality tests and mismatch distributions, indicated the occurrence of regulatory bottleneck-expansion cycles in the IGR, contrasted by signatures of purifying selection at the CP-MP junction. Quantitative PCR and bisulfite-PCR sequencing of the IGR region revealed that both the copy number of EPRVs and the level of cytosine methylation are differentially modulated in response to the cropping strategy.DiscussionThese findings provide new insights into the dynamic role of EPRVs in shaping plant responses to salt stress, whereas the intercropping approach emerged as an effective farming strategy for mitigating the adverse effects of salinity stress.